ISU STRATEGI PEMBIAYAAN DEFISIT ANGGARAN DI INDONESIA - Soebagiyo, Daryono (Universitas Muhammdaiyah Surakarta, 2012)
The issue of budget deficit financing strategy has been broad enough to gain attention in macroeconomic policy. This study is focused on Analysis of Budget Deficit Financing in Indonesia. How is the deficit financing management implemented such as what are the best sources and its contribution to the Indonesian economy. The study explains that the model used to estimate the impact indicators is capable to manage budget deficit financing, in which the variable domestic financing and external debt encourages the economic growth. Another research goal is to identify the amount of deficit financing sources and their effects on the economy. Under normal conditions in simulation 2. by increasing foreign financing about 15 percent, economic growth will increase about 1.40 percent, and inflation will fall about 0.11. In the crisis where the interest rate increased 15 percent and domestic financing increased with the same rate, economic growth will fall 0.08 and inflation 0.01 percent.